TEST CASE PRIORITIZATION WITH IMPROVED GENETIC ALGORITHM - Cingiz, M. Ozgur; Temel, Sefik; Kalipsiz, Oya (IEEE, 2014)
In software development, the most time consuming phase is maintenance. Regression testing, which is a part of maintenance, deals with test case prioritization that aims to increase rate of fault detection with less number of tests. In our study, we used 100 tests and 1000 faults; however, faults are detected by tests using genetic algorithm and improved genetic algorithm. After test case prioritization, we may detect all faults with less number of tests so there'll no need to apply all 100 tests (re-test).
Keywords: regression test; test case prioritization; genetic algorithms; hybrid algorithms; Engineering; Telecommunications